Media Awareness on Diseases from Pollution - A Study of Silchar Town in Southern Assam, India - Parthia Sarkar (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2021)
Exposures to environmental toxicants have always been a major source of health risks throughout the world. Pollution is thus a threat to human health, the environment and the quality of life of millions of lives on this planet. Since the last decade, media has become a major source in promoting health awareness. They provide knowledge about how to prevent and overcome from these diseases. The media matter significantly in public health. It affects the mind of the people as well as their thinking process and ideas. It is a major force in creating awareness about important issues and affects national and global efforts towards socio-economic progress and understanding. This descriptive cross sectional study was conducted to determine the awareness level and knowledge of the people of Silchar about pollution diseases and various health problems arising out of it.